Amphiphilic Cyclopeptide‐Dyes: Smart Self‐Assembly Amphiphilic Cyclopeptide‐Dye for Near‐Infrared Window‐II Imaging (Adv. Mater. 16/2021). Issue 16 (20th April 2021) - Chen, Hao; Shou, Kangquan; Chen, Si; Qu, Chunrong; Wang, Zhiming; Jiang, Lei; Zhu, Mark; Ding, Bingbing; Qian, Kun; Ji, Aiyan; Lou, Hongyue; Tong, Ling; et al.
Abstract : A small‐molecular‐based self‐assembling and pH‐responding NIR‐II fluorescent nanoprobe is developed by Zhenhua Hu, Jie Tian, Zhen Cheng, and co‐workers in article number 2006902 . This nanoprobe sharply responds to a decrease of pH in the tumor microenvironment. It aggregates from small nanoprobes (80 nm at pH 7.0) into large nanoparticles (>500 nm at pH 6.8), resulting in high tumor contrast and prolonged tumor retention (>19d). Thus, the bright clinical translational potential of small‐molecular self‐assembly nanoparticles is demonstrated.